Financial and Industrial Structure with Agency - Williams, Joseph T. (Review of Financial Studies, 1995)
[A subgame perfect Nash equilibrium is characterized for an industry with dissipative costs of agency. In sequence, firms can enter the industry, raise capital with external debt and/or equity, invest in a capital-intensive technology or dissipate capital in perquisites, and finally produce output. For plausible values of two critical parameters, some firms forego in equilibrium investments with positive net present values. Although more managers would like their firms to invest in the capital-intensive technology, they cannot raise the required cash in the capital market. In equilibrium, the industry can have both a profitable core of large, secure, capital-intensive firms, with some debt but no unique optimal capital structure, and a competitive fringe of small, risky, labor-intensive firms. Even as the cost of entry converges to zero, capital-intensive firms can earn extraordinary profits, while all labor-intensive firms fail. With costly agency, access to capital can become a barrier to entry.]